Perceptual watermarking and data concealment in audio signals - Tio, Cedric Meng Meng. (2008)
This project aims to hide data in audio streams by direct substitution of the FFT spectral lines with the hidden data. The spectral lines to be replaced are carefully chosen with the help of a psychoacoustic model. The model characterizes the behaviour of our ear with mathematical equations.